Revisit "The Grapes of Wrath" - Alves, Isabel Maria Fernandes (2023)
This proposal aims to revisit John Steinbeck’s novel The Grapes of Wrath, published in 1939. The analysis will focus on the way the work asserts itself, even today, as a between-place, a literary space where humanity faces change – social, geographical, climatic, and a deep division between the powerful and the marginalized. In other words, a contemporary reading of the novel is proposed, with the aim of highlighting how Steinbeck, conscious of the interdependence of humans and other forms of life, as well as of the increasing vulnerability of organisms under human action, imagined characters and developed themes that help us to (re)think our time.Revisiting The Grapes of Wrath in the twentieth-first century constitutes a stimulating exercise. The issues of that time remain pertinent, particularly the idea of change. The theme of transformation plays an important role throughout the narrative, not only through the physical and spiritual displacement of the characters, but also in calling for a change in the reader’s mentality, an evolution required for a more harmonious and healthier co-inhabitation of the Earth. Ultimately, in The Grapes of Wrath the characters cross multiple borders, breaking down walls that separate the human and the non-human, inciting the reader to ponder different ways of (better) inhabiting the Earth, giving voice to what Aldo Leopold termed as “biotic community”.